2017
DOI: 10.1007/s12243-017-0587-2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-domain identity and discovery framework for web calling services

Abstract: Cross-domain identity management remains a major challenge for potential WebRTC adopters. In order to provide a global web-based communication system, it is critical to locate the destination called party, map the identity to the user device, and provide mutual authentication for both caller and called party. In this paper, we present a novel identity management and user discovery framework that enables callers to search and locate users across service domains. The identity management is decoupled from the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In centralized IdM, the identity provider has complete control to manage the identity of users and provide them authentication services. Most of the current services and applications use centralized IdM to create a silo of users where users identified in a specific domain cannot authenticate themselves to other domains [6]. Federated IdM, on the other hand, is an arrangement between two or more organizations to allow users from one domain to authenticate and access services of other domains [26], for instance, single-sign-on systems such as Facebook connect [27].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In centralized IdM, the identity provider has complete control to manage the identity of users and provide them authentication services. Most of the current services and applications use centralized IdM to create a silo of users where users identified in a specific domain cannot authenticate themselves to other domains [6]. Federated IdM, on the other hand, is an arrangement between two or more organizations to allow users from one domain to authenticate and access services of other domains [26], for instance, single-sign-on systems such as Facebook connect [27].…”
Section: Related Workmentioning
confidence: 99%
“…The centralized IdM creates silos of users restricting inter-operable identification between different applications [6]. For each application, the consumer has to identify and authenticate themselves separately.…”
Section: Introductionmentioning
confidence: 99%
“…They therefore concluded that secure browsers are essential in preventing existing vulnerabilities. Other studies such as the ones in [24], [53] and [54] have also emphasized web system hardening in mitigating attacks. According to [55], secure web systems are characterized by three components; input validity, state integrity and logic correctness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a single patient’s identity data may be distributed in multiple healthcare service institutions, and the information cannot be interoperable between them. The identity authentication management of patients is isolated [ 5 ], i.e., patients need to register different digital identities between institutions [ 6 ]. Thus, when patients visit the institution, some operations, such as information recovery and repeated registration, are inevitable because they forget the account.…”
Section: Introductionmentioning
confidence: 99%